Functional Comparison of Clostridium butyricum and Sodium Butyrate Supplementation on Growth, Intestinal Health, and the Anti-inflammatory Response of Broilers - Liu, Ling; Ling, Huayun; Zhang, Wei; Zhou, Ying; Li, Youguo; Peng, Nan; Zhao, Shumiao (Frontiers in Microbiology, 2022)
Butyrate has been reported to promote proliferation of colonic epithelial cells and maintain intestinal barrier integrity in broilers. Although supplementation of Clostridium butyricum and sodium butyrate have been shown to confer benefits on broilers, their effects and mechanisms have not been compared. In this study, C. butyricum and sodium butyrate were added into the basal diet of broilers and their effects on growth performance, intestinal health, and anti-inflammatory response were analyzed. It was found that both C. butyricum and sodium butyrate showed good probiotic effects on broilers. Their effects on growth rate and expression of inflammation related genes were superior to that of the antibiotic oxytetracycline. Besides, the two dietary supplements improved intestinal structure integrity and secretion of inflammatory cytokines, whereas the antibiotic had negative effects. Comparison of the two supplements revealed that sodium butyrate more effectively improved the growth and intestinal structure of broilers than C. butyricum. On the contrary, C. butyricum was superior to sodium butyrate in promoting tight junction protein expression and anti-inflammatory response. In summary, this study demonstrates the positive effects of C. butyricum and sodium butyrate on broilers, and will serve as a reference for selection of appropriate butyrate supplementation for broilers in the breeding industry.